Enhancing Sustainable Market Competitiveness through Innovation, Service Optimization, and Brand Management: The Mediating Role of Differentiation in Beijing’s Printing Industry - Li, Peng; Siriwattana, Srochinee (International Journal of Development Administration Research, 2025)
This research combines both quantitative and qualitative methods, research design, and research environment for investigating the influence of technological innovation capability, service system optimization, and brand management on sustainable market competitiveness in Beijing printing enterprises, with a focus on the mediating role of enterprise competitive differentiation capability. Research Objectives: (1) To evaluate current levels of technological innovation capability, service system optimization, brand management, and enterprise differential competitive capability among Beijing printing enterprises through descriptive statistics and benchmarking analysis. (2)To examine the mediating role of enterprise differential competitive capability in the relationships between technological innovation capability, service system optimization, brand management, and sustainable market competitiveness using structural equation modeling (SEM). (3)To validate an integrated SEM model for enhancing sustainable market competitiveness of Beijing printing enterprises through technological innovation capability, service system optimization, brand management, and enterprise differential competitive capability. Literature Review use: Resource - Based Theory, Institutional Theory. Enterprise Sustainable Development Theory, Technological Innovation Capability, Technological Innovation Capability and their Dimensions. Definition of Service System Optimization: And Definition of Brand Management. This study shows that technological innovation capability, service system optimization, and brand management each play crucial roles in enhancing sustainable market competitiveness in Beijing’s printing industry. Across all three areas, enterprise differentiation capability serves as the key mediating mechanism that transforms these capabilities into competitive advantages. Technological innovation contributes not only through efficiency and quality improvements but also through environmental gains that strengthen green differentiation. Service system optimization enhances competitiveness via operational coordination, stronger customer relationships, and sustainability benefits, producing durable, capability-embedded differentiation. Brand management acts as a strategic asset by signaling credibility and sustainability, helping firms secure price premiums and client loyalty. Differentiation emerges as a dynamic capability rather than a simple strategic choice, converting diverse organizational resources into market advantages. The effectiveness of these mechanisms depends on industry context, enterprise size, and market segment. The study also shows that technology, service, and brand capabilities each support different dimensions of sustainability, requiring balanced development. Overall, sustainable competitiveness in traditional industries hinges on integrating technological, service, and brand capabilities and aligning them with firm strengths and market conditions.